The h(Â³) â€“ index of academic journals - Fassin, Yves; Rousseau, Ronald (Malaysian Journal of Library and Information Science, 2019)
The objective of this paper is to show that the already existing h(³) indicator, designed after the h- index and Kosmulski’s h(²)-index, has some advantages with respect to the classical h- or h(²)-indices, when it comes to academic journal evaluation. The h(³)-index for journals is defined as the largest natural number h3 such that the first h3 publications each received at least (h3)3 citations. Because of its tough requirement it is difficult to have a high h(3)-index. Consequently, this index is more selective than the classic h and h(2)-indexes. It enjoys a greater stability and is simple to determine as it necessitates only a small number of most-cited articles of a journal and varies only every 2 to 5 years. We admit though that like many other indicators the h(3) indicator is only PAC (Probably Approximately Correct). Yet, it is proposed as a simple and valuable alternative to the more complex and contested Journal Impact Factor.